Unchanged anaerobic and aerobic performance after short-term intermittent hypoxia - Tadibi, V.; Dehnert, C.; Menold, E.; Bärtsch, P. (Medicine & Science in Sports & Exercise, 2007)
Introduction: Repeated short-term exposures to a severe degree of hypoxia, alternated with similar intervals of normoxia, are recommended for performance enhancement in sports. However, scientific evidence for the efficiency of this method is controversial with regard to anaerobic performance. Therefore, we conducted a randomized, double-blind, placebo-controlled study to investigate the effects of this new method on both anaerobic and aerobic performance.